Observation and Ecology : Broadening the Scope of Science to Understand a Complex World. - Sagarin, Rafe (Springer, 2012)
The need to understand and address large-scale environmental problems that are difficult to study in controlled environments-issues ranging from climate change to overfishing to invasive species-is driving the field of ecology in new and important directions. Observation and Ecology documents that transformation, exploring how scientists and researchers are expanding their methodological toolbox to incorporate an array of new and reexamined observational approaches-from traditional ecological knowledge to animal-borne sensors to genomic and remote-sensing technologies-to track, study, and unde.